Interseksi Hak Asasi Manusia dan Sharī'ah di Indonesia - Syamsul Arifin; Nafik Muthohirin; Tongat Tongat; Wahyudi Wahyudi (Islamica: Jurnal Studi Keislaman, 2018)
This article attempts to uncover the point of encounter of human rights and sharī'ah in Indonesia which often contradict with each other in light of differences in its development base, both as a concept and, furthermore, as an instrument, which ultimately leads to the human dimension. The basis of the development in question is that human rights derived from human rationality, while sharī'ah comes from revelation. Therefore, this article seeks to explore the compatibility between the two. Human rights and sharī'ah always have a point of encounter because in principle they are both fighting for humanity. The intersection between the two is often the case--and it becomes common because the basis for the development of the law originates from different sources. Human rights comes from human rationality, while sharī'ah departs from Allah's revelation. Thus, it is only natural that various debates arise as in general a discourse of knowledge. It's just that it needs to be understood that the conflict and tension that arise, should not lead to violence. On the one hand, Muslim groups who reject the principles of human rights are undoubtedly existent. However, on the other hand, many Muslims also graciously accept human rights. Accommodative people hold the view that they have a common vision of justice, peace, equality, and tolerance. Human rights need not be viewed as contradictory to Islam, in part because many Muslim-majority countries recognize and ratify human rights instruments issued by the United Nations.